2003
DOI: 10.1007/bf03033173
|View full text |Cite
|
Sign up to set email alerts
|

The vitamin-E analog trolox and the NMDA antagonist MK-801 protect pyramidal neurons in hippocampal slice cultures from IL-1β-induced neurodegeneration

Abstract: The neurotoxic effect of the pro-inflammatory cytokine interleukin (IL)-1beta was studied in monolayer cultures, obtained using roller-drum incubation of hippocampal slices from neonatal Sprague Dawley rats. Following exposure to recombinant rat IL-1beta for four days, a concentration dependent loss was observed in the number of NMDAR1 receptor subunit immunoreactive pyramidal neurons in the cultures, reaching significance at 10 ng/ml rIL-1beta. Also incubation with recombinant mouse IL-1beta caused a loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 51 publications
(64 reference statements)
0
17
0
Order By: Relevance
“…IL-1ß per se is neurotoxic and its effects are apparently mediated through NMDA excitotoxins such as quinolinic acid (Fornstedt-Wallin et al, 1999), possibly derived from astrocytes (Guillemin et al, 2000) or microglia (Alberati-Giani et al, 1996). In order to study putative neuroprotective effects of the NMDA receptor antagonist dizocilpine (MK-801) and the vitamin E analog trolox on hippocampal pyramidal neurons (which possess IL-1 receptors), Radesäter et al (2003) …”
Section: Effect Of Trolox and Nmda On Il-1ß-induced Neurodegenerationmentioning
confidence: 99%
“…IL-1ß per se is neurotoxic and its effects are apparently mediated through NMDA excitotoxins such as quinolinic acid (Fornstedt-Wallin et al, 1999), possibly derived from astrocytes (Guillemin et al, 2000) or microglia (Alberati-Giani et al, 1996). In order to study putative neuroprotective effects of the NMDA receptor antagonist dizocilpine (MK-801) and the vitamin E analog trolox on hippocampal pyramidal neurons (which possess IL-1 receptors), Radesäter et al (2003) …”
Section: Effect Of Trolox and Nmda On Il-1ß-induced Neurodegenerationmentioning
confidence: 99%
“…LPS has also been shown to induce the expression of IL-1β in mixed glial cell cultures (Chauvet et al, 2001). This finding is of particular relevance in the present context, since we have previously shown that IL-1β is neurotoxic to NMDA-R1 immunoreactive cells in hippocampal roller-drum cultures (Luthman et al, 1998;Radesäter et al, 2003). Activation of microglia and macrophages, causing a production of different neurotoxic factors, may therefore be critically involved in LPS-mediated neurodegeneration in hippocampal slice cultures.…”
Section: Discussionmentioning
confidence: 80%
“…With LPS as a tool to induce general inflammatory reactions, possibilities are presented to study the link between inflammation and neurodegeneration. For example, we have been able to induce both IL-1β (Luthman et al, 1998;Radesäter et al, 2003) and Aβ peptide- (Johansson et al, 2005) mediated neurodegeneration in the culture system used in the present study. Neuroinflammation, APP processing and Aβ neurotoxicity may in fact be related.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…27,28) Neuroprotective effect of trolox is further supported by its protective effect in amyloid b-mediated neurotoxicity, 29) and interleukin (IL-1b) induced neurodegeneration. 30) In addition to protective effects in neurotoxicity models, trolox counteracted the toxic effects of S-morpholinosydnonimine (SIN-1), a peroxynitrite donor in lung epithelial cells, 31) and in arrhythmias in isolated heart preparations. 32) Consistent with the earlier reports, we have also observed significant increase in the level of MDA in ischemic animals indicating oxidative stress.…”
Section: Discussionmentioning
confidence: 99%